2017
DOI: 10.1111/trf.14080
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusions can induce proinflammatory cytokines in preterm infants

Abstract: BACKGROUND The risk of developing red blood cell (RBC) transfusion–associated necrotizing enterocolitis (TANEC) in preterm infants has recently been emphasized. Our aim was to assess changes in cytokine serum levels after RBC transfusions in a cohort of very preterm infants to evaluate their possible proinflammatory effect. STUDY DESIGN AND METHODS We carried out a prospective observational study. One transfusion event was studied in infants less than 32 weeks' gestation and more than 7 days old (n = 20) admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 42 publications
(78 reference statements)
4
58
1
1
Order By: Relevance
“…As our recent study demonstrated that anemia alone correlated with NEC irrespective of RBC transfusion, these results guided the focus of the current study. However, given the present findings and recent studies suggesting that transfusion may also impact neonatal immune function, future studies will be needed to decipher appropriate hemoglobin thresholds and optimal transfusion protocols to reduce or prevent anemia‐induced intestinal inflammation and injury.…”
Section: Discussionmentioning
confidence: 94%
“…As our recent study demonstrated that anemia alone correlated with NEC irrespective of RBC transfusion, these results guided the focus of the current study. However, given the present findings and recent studies suggesting that transfusion may also impact neonatal immune function, future studies will be needed to decipher appropriate hemoglobin thresholds and optimal transfusion protocols to reduce or prevent anemia‐induced intestinal inflammation and injury.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, significant immunomodulation occurs in infants after transfusion of allogeneic RBCs, leading to increased expression of proinflammatory cytokines [e.g. interleukin (IL)‐1, IL‐8] and markers of endothelial activation (Keir et al , ; Dani et al , ). Studies have shown that continuation of enteral feed during RBC transfusion blunts post‐prandial mesenteric hyperaemia for up to 48 h after transfusion (Marin et al , ).…”
Section: When Do We Give Rbc Transfusions For Anaemia Of Prematurity?mentioning
confidence: 99%
“…Dani et al [76] prospectively examined 20 infants with a gestational age < 32 weeks and measured serum levels of various cytokines before and at various time points after RBCT up to 48 h post-RBCT. That small study showed a significant increase in IL-1β, IL-8, IFN-γ, IL-17, MCP-1, IP-10, and ICAM-1 after RBCT.…”
Section: Anaemia Blood Transfusion and Necmentioning
confidence: 99%